2021
DOI: 10.3389/fphys.2021.672457
|View full text |Cite
|
Sign up to set email alerts
|

Biological Prescience: The Role of Anticipation in Organismal Processes

Abstract: Anticipation is the act of using information about the past and present to make predictions about future scenarios. As a concept, it is predominantly associated with the psychology of the human mind; however, there is accumulating evidence that diverse taxa without complex neural systems, and even biochemical networks themselves, can respond to perceived future conditions. Although anticipatory processes, such as circadian rhythms, stress priming, and cephalic responses, have been extensively studied over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 192 publications
(254 reference statements)
1
9
0
Order By: Relevance
“…As embodied cognitive morphogenesis is about bridging developmental biology with emergent cognition, we are in a unique position to stake out a novel stance on 4E cognition. Both in the morphogenetic process itself and in the emergence of cognition, anticipatory mechanisms [97] and complex self-assembly mechanisms [98] become important. From the developing organism's perspective, the resulting tensegrity leads not only to structural stability, but stability during subsequent transformations.…”
Section: Discussionmentioning
confidence: 99%
“…As embodied cognitive morphogenesis is about bridging developmental biology with emergent cognition, we are in a unique position to stake out a novel stance on 4E cognition. Both in the morphogenetic process itself and in the emergence of cognition, anticipatory mechanisms [97] and complex self-assembly mechanisms [98] become important. From the developing organism's perspective, the resulting tensegrity leads not only to structural stability, but stability during subsequent transformations.…”
Section: Discussionmentioning
confidence: 99%
“…As embodied cognitive morphogenesis is about bridging developmental biology with emergent cognition, we are in a unique position to stake out a novel stance on 4E cognition. Both in the morphogenetic process itself and in the emergence of cognition, anticipatory mechanisms [83] and complex self-assembly mechanisms [84] become important. From a developmental perspective, tensegrity leads not only to structural permanence, but stability during subsequent transformations.…”
Section: E Cognition Provides a Route To Cognitive Systemsmentioning
confidence: 99%
“…Anticipatory behavior (henceforth AB) refers to the ability of an organism to coordinate its behavior with one or more future environmental or organismal states, proactively influencing how or whether such states occur. Such behavior has been of great interest to cognitive science and psychology because it has often been seen as indicative of cognition (Bartlett 1932;Craik 1943;Piaget 1970;Neisser 1976;Drescher 1991;Arbib 1992;Castelfranchi 2005;Lyon 2006 ;Pezzulo 2008 ;Bickhard 2009;Deacon 2012;Clark 2016;Corcoran et al 2020;Sims 2021). Interestingly, within the last 30 years various biological studies have suggested that AB is not limited to neuronal organisms but may also be exhibited by organisms such as bacteria (Schild et al 2007;Tagkopoulos et al 2008), fungi (Mitchell et al 2009;Rodaki et al 2009), acellular slime mold (Saigusa et al 2008), amoebae (De la Fuente et al 2019), and plants (Novoplansky et al 1990;Latzel and Münzbergová 2018).…”
Section: Introductionmentioning
confidence: 99%